2018
DOI: 10.1002/dys.1600
|View full text |Cite
|
Sign up to set email alerts
|

Auditive training effects from a dichotic listening app in children with dyslexia

Abstract: Dichotic listening (DL) taps information on the brain's language laterality, processing, and attention. Research has shown that DL responses in dyslexia deviate from the typical pattern. Here, effects of DL training and its correspondence to rapid naming (RAN) and digit span (DS) in typical children and children with dyslexia were assessed. Three groups of third graders participated: two training groups, control training (CT) and dyslexia training (DT), and a control group that received no training (control no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 62 publications
(117 reference statements)
2
15
0
Order By: Relevance
“…Critically, the amenability of Selective auditory attention performance to training is not limited to these highly-selective groups. Improvement in Selective Attention performance has been demonstrated after a 4-week dichotic-listening training program in healthy adults (Soveri et al, 2013), and similar training effects have been reported in typically developing children (Murphy, Moore, & Schochat, 2015), as well as children with dyslexia (Helland et al, 2018). These findings point to the flexible nature of auditory Selective Attention, which can be improved through formal training programs and as well as frequent practice (Mishra, de Villers-Sidani, Merzenich, & Gazzaley, 2014).…”
Section: The Comparison Between Selective and Distributed Attention Isupporting
confidence: 58%
“…Critically, the amenability of Selective auditory attention performance to training is not limited to these highly-selective groups. Improvement in Selective Attention performance has been demonstrated after a 4-week dichotic-listening training program in healthy adults (Soveri et al, 2013), and similar training effects have been reported in typically developing children (Murphy, Moore, & Schochat, 2015), as well as children with dyslexia (Helland et al, 2018). These findings point to the flexible nature of auditory Selective Attention, which can be improved through formal training programs and as well as frequent practice (Mishra, de Villers-Sidani, Merzenich, & Gazzaley, 2014).…”
Section: The Comparison Between Selective and Distributed Attention Isupporting
confidence: 58%
“…Improvement in selective attention performance has been demonstrated after a 4-week dichotic-listening training program in healthy adults (Soveri et al, 2013), and similar training effects have been reported in typically developing children (C. F. B. Murphy, Moore, & Schochat, 2015), as well as children with dyslexia (Helland et al, 2018). Admittedly, in the current study we cannot exclude the possibility that the pilot's advantage on selective attention may not be solely due to their flight experience, and there may be additional non-flight-related differences between the groups (not captured by controlling for WMC and g factor).…”
Section: Professional Experiencesupporting
confidence: 56%
“…Verbal dichotic-listening paradigms offer well-established behavioral tests for the assessment of latent hemispheric differences for language processing [1,2] and are integral part of test procedures for the diagnosis of auditory processing disorders [3][4][5]. A significant advantage of dichotic compared with alternative paradigms (e.g., visual-half field techniques or neuroimaging approaches) is the simplicity of the testing procedure which can be easily understood and performed also by young children [e.g., 6,7], elderly individuals [e.g., 8,9], or patients with cognitive disabilities [e.g., 10,11]. That is, in its basic form, pairs of verbal stimuli (e.g., words or syllables) are presented via headphones, with one of the stimuli presented to the left ear and the other one, simultaneously, to the right ear [12].…”
Section: Introductionmentioning
confidence: 99%